2004
DOI: 10.1213/01.ane.0000104610.99716.37
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Oral Dextromethorphan Attenuated Tourniquet-Induced Arterial Blood Pressure and Heart Rate Increases in Knee Cruciate Ligament Reconstruction Patients Under General Anesthesia

Abstract: We demonstrated that preoperative oral dextromethorphan 30 mg significantly attenuated arterial blood pressure and heart rate increases at 60 min during tourniquet inflation in patients undergoing knee cruciate ligament reconstruction under general anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
(22 reference statements)
0
11
0
Order By: Relevance
“…16 During lower extremity procedures, different agents such as dextromethorphan, clonidine, remifentanil, and ketamine were used to prevent tourniquet-induced pain. 11,[17][18][19] In a study that compared dextromethorphan and clonidine for blunting the tourniquet-induced cardiovascular response during lower extremity procedures under general anesthesia, it was demonstrated that preoperative oral clonidine significantly decreased systolic, diastolic, and mean arterial pressures. 20 The study of Park et al demonstrated that preoperative low dose ketamine administration (0.1 mg.kg -1 ) is effective in the treatment of tourniquetinduced hypertension for 60 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…16 During lower extremity procedures, different agents such as dextromethorphan, clonidine, remifentanil, and ketamine were used to prevent tourniquet-induced pain. 11,[17][18][19] In a study that compared dextromethorphan and clonidine for blunting the tourniquet-induced cardiovascular response during lower extremity procedures under general anesthesia, it was demonstrated that preoperative oral clonidine significantly decreased systolic, diastolic, and mean arterial pressures. 20 The study of Park et al demonstrated that preoperative low dose ketamine administration (0.1 mg.kg -1 ) is effective in the treatment of tourniquetinduced hypertension for 60 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the delayed hypertension observed with the use of a tourniquet is known to be related to NMDA receptor activation by peripheral noxious stimuli from the extremities and occurs 40-60 min after inflation 5,6.…”
Section: Discussionmentioning
confidence: 99%
“…The tourniquet induced hypertension (TIH) is usually delayed 30-60 min after tourniquet inflation [5], and it is difficult to treat even with adequate analgesia and good level of anesthesia [6,7]. Although the proper mechanism of (TIH) is still unclear [7], the autonomic nervous system is probably involved and plasma catecholamine levels are increased [2].…”
Section: Introductionmentioning
confidence: 99%
“…Also, stimulation of N-methyl-D-Aspartate (NMDA) receptors by noxious stimuli from the extremities is another possible cause leading to TIH [8,9]. There are several studies done using different analgesics and NMDA receptor antagonists to find an effective drug to attenuate (TIH) [6][7][8]5].…”
Section: Introductionmentioning
confidence: 99%